The bright and the dark sides of a working day: significant daily events and emotional activation: the role of cognitive appraisals - Junça Silva, A.; Caetano, António; Lopes, M. (17th congress of the European Association of Work and Organizational Psychology (EAWOP), 2015)
In this study, we investigated predictors of the activation of emotional reactions relying on the theoretical frameworks of affective events theory and the cognitive appraisal theory. Past research has pointed out the relevance of cognitive appraisals in the link between events and emotions, such as, the appraisal of the event’s importance and its intrinsic pleasantness. However, no study has explored whether the interaction of both cognitive appraisals affect the relationship between affective events and emotional activation. We posited that cognitive appraisals of the events’ self-importance and intrinsic pleasantness may act as key moderating factors influencing employees’ emotional activation prompted by daily events. A 3-way interaction between daily events (hassles and uplifts), cognitive appraisals of importance and intrinsic pleasantness on emotional activation was hypothesized. We collected qualitative and quantitative data from 87 full-time employees on significant work-related daily events (hassles and uplifts), cognitive appraisals of the events’ self-importance and intrinsic pleasantness and emotional reactions to work events. Results showed that the cognitive appraisal of the event’s importance moderated the relationship between daily uplifts and emotional activation: the positive relationship was stronger when daily uplifts were appraised as highly important. However, the intrinsic pleasantness did not moderate this relationship. Results supported the 3-way interaction hypothesized for daily hassles. The findings suggest that appraisals of an event’s importance and intrinsic (un)pleasantness influence the link between daily events and its emotional activation differently for daily hassles and uplifts. These findings provide a promising avenue for research on daily events at work. Additionally, there is strong potential for practical application within organizations regarding job-designing, performance management, and training.